Discriminatory power of water polo game-related statistics at the 2008 Olympic Games - Escalante, Y.; Saavedra, J. M.; Mansilla, M.; Tella, V. (Journal of Sports Sciences, 2011)
The aims of this study were (1) to compare water polo game-related statistics by context (winning and losing teams) and sex (men and women), and (2) to identify characteristics discriminating the performances for each sex. The game-related statistics of the 64 matches (44 men's and 20 women's) played in the final phase of the Olympic Games held in Beijing in 2008 were analysed. Unpaired t-tests compared winners and losers and men and women, and confidence intervals and effect sizes of the differences were calculated. The results were subjected to a discriminant analysis to identify the differentiating game-related statistics of the winning and losing teams. The results showed the differences between winning and losing men's teams to be in both defence and offence, whereas in women's teams they were only in offence. In men's games, passing (assists), aggressive play (exclusions), centre position effectiveness (centre shots), and goalkeeper defence (goalkeeper-blocked 5-m shots) predominated, whereas in women's games the play was more dynamic (possessions). The variable that most discriminated performance in men was goalkeeper-blocked shots, and in women shooting effectiveness (shots). These results should help coaches when planning training and competition.